Pengaruh Laba dan Arus Kas Terhadap Harga Saham pada Perusahaan Manufaktur Sub Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia - Martina Jerahu; Meldilianus N.J Lenas; Andi Herman Tellu (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2025)
This study aims to determine the effect of net profit and cash flow on stock prices in pharmaceutical companies listed on the Indonesia Stock Exchange in 2019 - 2023. This research approach uses an associative research approach. The population in this study are companies engaged in the pharmaceutical sector listed on the Indonesia Stock Exchange in 2019 - 2023, totaling 10 companies. The sample that meets the criteria in this study is 7 pharmaceutical companies listed on the Indonesia Stock Exchange in 2019 - 2023. The data collection technique in this study is a documentation study. The data analysis technique in this study is descriptive statistics, classical assumption tests including normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests, multiple linear regression analysis, hypothesis testing including t-tests, f-tests and coefficients of determination. The results of this study indicate that partially net profit does not affect stock prices in pharmaceutical companies listed on the Indonesia Stock Exchange in 2019 - 2023, partially cash flow does not affect stock prices in pharmaceutical companies listed on the Indonesia Stock Exchange in 2019 - 2023, then net profit and cash flow simultaneously affect stock prices in pharmaceutical companies listed on the Indonesia Stock Exchange in 2019 - 2023.